Affect and desire: museums and the cinematic - Baker, Janice (Curtin University, 2010)
The museum continues to be broadly framed in the critical literature in terms of its Enlightenment legacy and related knowledge/power relations. To contend with this authoritative institutional legacy, critical theory within the new museology operates to ensure museums are inclusive of class, race, gender, creed and identity. Yet this vigilant, didactic focus on inclusivity limits the ability of the museum to engage in transformative, affecting ways with the very idea of alterity that is fundamental to any inclusive agenda.As a theoretical investigation of museums and the cinematic, this thesis considers the potential for museum studies of engaging with affect and desire alongside the rational, inclusive museum. Two modes of affecting encounter are conceptualised to illuminate the resonance of affect in museums; the intentional use of didactic affect and the serendipitous intensity of non-discursive affect. Didactic affect arises from recognition and emotion, and is aligned to common sense notions of time, memory and history. However, affect is also generated outside didactic, discursive intent. This mode of affectivity assumes credibility in fictional museums presented in films; resoundingly these museums are sites of non-conformity, seduction and the irrational.Drawing on Gilles Deleuze’s interest in cinema images and the production of new thought, the thesis appraises fictional museums in films. Deleuze rejects Lacanian influenced cinema analysis and the axiom that desire is pre-programmed within an already structured and repressed Oedipal unconscious. In the focus on repression and ideology, there is parallel between the limitation of cine-psychoanalytical approaches to museums in films and structuralist approaches to actual museums in the critical literature. An anti-Oedipal approach to the affective museum assembles visitors and artefacts not according to the subject/object dichotomy of structuralist modes of understanding but as desiring-machines capable of unfolding alternative ways of thinking the relation of the human and nonhuman. As such the thesis offers an ethico-aesthetic dimension for critical engagement with the field of museum studies.